PS02.048: DECREASED EXPRESSION OF PRSS27 IN ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (14th September 2018) - Terayama, Masayoshi; Hagiwara, Teruki; Yamada, Kazuhiko; Soma, Daisuke; Nohara, Kyoko; Yamashita, Satoshi; Kokudo, Norihiro; Dohi, Taeko; Kawamura, Yuki I
Abstract: Background: Alcohol drinking and smoking are substantial risk factors of esophageal squamous cell carcinoma (ESCC) and are supposed to induce genetic mutations and epigenetic disorders, including aberrant DNA methylation. Previously, we have conducted transcriptome and methylome analyses of a paired specimen of ESCC and adjacent non-cancerous tissues and found that both gene expression and promotor methylation of PRSS27 were perturbed in ESCC. PRSS27 was a trypsin-like serine protease (also known as marapsin) and expressed in normal esophagus; however, little is known about the significance of PRSS27 expression in ESCC. In this study, we evaluated the expression of PRSS27 in many ESCC cases in relation with clinical features and the prognosis. Methods: ESCC tissue specimens were obtained from 80 patients who had undergone esophagectomy between April 2008 and December 2016 in our hospital and were subjected to immunostaining for PRSS27. ESCC cases were classified into PRSS27-negative and PRSS27-positive groups and difference of clinical features and the prognosis between the groups was analyzed. Results: The mRNA expression of PRSS27 was significantly decreased in ESCC compared with those in matched normal mucosa ( P  < 0.0001). Histologically, PRSS27 was highly expressed in spinous cells of suprabasal cell layer but not in basal cell layer of normal esophageal mucosa. In contrast, 37 of 80 (47%) ESCC exhibited decreased intensity of PRSS27 staining when compared with that in normal mucosa, and 53% (43/80) of ESCC showed almost no staining of PRSS27. Although the prognosis of PRSS27-positive cases were worse in trend than that of PRSS27-negative cases, there was no significant difference ( P  = 0.0763) Conclusion: PRSS27 gene and protein expression was both downregulated in ESCC; its functional significance in relation to malignancy is underinvestigation. Disclosure: All authors have declared no conflicts of interest.